Investigating the optimal duration of maternity leave: Evidence from the Parental Leave in Australia Survey - Hosking, A; Whitehouse, G; Baird, M (My University, 2007)
This presentation explores gender equity outcomes in paid employment, based on maternity leave users' experiences and perceptions from 'The Parental Leave in Australia Survey'. The survey was distributed with the infant cohort of the 'Longitudinal Study of Australian Children' (LSAC) in 2005, and received 3,568 responses. The presentation consists largely of charts on the survey responses, including duration of paid and unpaid maternity leave usage in Australia, mothers' perceptions of satisfaction with leave duration, and perceptions of career opportunities after returning to work, and graphs of the logistic regression results on the likelihood and probability of various results.
Keywords: Employment; Employment -- Parental leave; Labour market; Employment; Parental leave; Employment and unemployment